COMPARATIVE BUSINESS OF RICE FARMING IN UMONG PAYA WITH UMONG LAND IN LEMBAH DISTRICT SABIL DISTRICT OF SOUTHWEST ACEH - Asrol Fajri; Zuriani; Irada Sinta (Universitas Efarina, 2022)
Lembah Sabil subdistrict there are two types of : rice fields, namely Umong Paya and Umong Darat, so there is a rice farming business that uses both lands. Is there a difference (comparative) in the benefits of rice farming using Umong Paya and Umong Darat. The purpose of this study was to determine the difference between the benefits of Umong Paya and Umong Darat rice farming. The location of this research was carried out in the Lembah Sabil subdistrict, Southwest Aceh Regency, especially in the two Gampong Cot Bak U and Meunasah Sukon carried out in 2022. The data analysis used in this study were cost calculations, acceptance calculations, profit calculations and different tests or tests. t (independent t test). The results of the research conducted explained that the rice farming business Umong Paya obtained an average production of 6,555 Kg/HA/MT, the average total cost of Rp. 18,930,106/Ha/MT, the average receipt of Rp. 32,217,411/Ha /MT and an average profit of Rp.13,287,305/Ha/MT. While Umong Darat rice farming business earned an average production of 7,704 Kg /Ha/ MT, the average total cost of Rp.16,305,657/Ha/MT, the average receipt of Rp. 34,766,457/Ha/MT, and an average profit of Rp. 18,462,758/Ha/MT. The analysis of data using the t test (independent t test), showed that the sig value of 0.016 < from 0.05 (????) means that there is a difference in the average profit of Umong Paya rice farming business with Umong Darat. Thus there is a difference in the average production, acceptance, total cost obtained by Umong Paya rice farming business with Umong Darat, resulting in a difference in profits obtained by the two farming businesses. The analysis of data that has been done shows that there is a real difference in the average profit in real terms between the Umong Paya rice farming business and Umong Darat in Lembah Sabil subdistrict of Southwest Aceh regency.